Mapping the intellectual structure and international collaboration in transportation research: A bibliometric analysis from Scopus top-tier journals - Kulyntay, Gaziz; Kushkumbayev, Aibolat; Chukubayev, Yermek; Shunayeva, Sylu (Iberoamerican Journal of Science Measurement and Communication, 2025)
Objective. We examined the intellectual structure and patterns of scientific collaboration in the field of transportation based on the publications published in the 10% of journals with the highest impact in Scopus. Design/Methodology/Approach. We performed a bibliometric analysis of scientific production in the field of transportation. The sample consisted of articles published between 2015 and 2024 in the 10% of journals with the highest impact in Scopus for this area, resulting in a final sample of 39 journals. The data were processed in Gephi software, where network maps were constructed and centrality metrics were calculated. Results/Discussion. The co-word map showed the centrality of terms related to road safety, infrastructure planning, and sustainability. These clusters reveal how current transportation research combines technical perspectives with interdisciplinary approaches, linking transportation engineering with public health and risk management. It was observed that the papers with the highest centrality were related to methodological studies in transportation modeling, as well as to research on resilience and vulnerability of systems. In terms of international collaboration between countries, the results corroborate trends noted by previous studies. The leadership of the United States, China, and the United Kingdom, with central positions in the collaborative network. Conclusions. The results of this study confirm that transportation research is moving towards a greater integration of multidisciplinary approaches, where road safety and sustainability are consolidated as cross-cutting issues.